Porcelain : a history from the center of Europe - Marchand, Suzanne L. (Princeton University Press, 2020)
Porcelain was invented in medieval Chinabut its secret recipe was first reproduced in Europe by an alchemist in the employ of the Saxon king Augustus the Strong. Saxonys revered Meissen factory could not keep porcelains ingredients secret for long, however, and scores of Holy Roman princes quickly founded their own mercantile manufactories, soon to be rivaled by private entrepreneurs, eager to make not art but profits. As porcelains uses multiplied and its price plummeted, it lost much of its identity as aristocratic ornament, instead taking on a vast number of banal, yet even more culturally significant, roles. By the nineteenth and twentieth centuries, it became essential to bourgeois dining, and also acquired new functions in insulator tubes, shell casings, and teeth.